Sistem Informasi Pendaftaran Santri Di Pondok Pesantren Al-Wathoniyah 43 Jakarta Utara Berbasis Web Dengan Fitur Whatsapp Gateway - Rahma Putri, Mega; Ghofur, Abd; Azise, Nur (Computer Science and Information Technology, 2024)
Islamic boarding schools, being traditional Islamic educational institutions in Indonesia, may face the problem of lack of access to technology. In Al-Wathoniyah Islamic Boarding School 43 North Jakarta, access to modern technology is still limited. Apart from this, data retrieval and processing is also slow (in manual systems, retrieval and processing of student data is a slow process and takes a long time). Since the registration of students in Al-Wathoniyah Islamic Boarding School 43 North Jakarta is still manual, it has several weaknesses such as. High energy requirements, relatively long or time-inefficient time, information errors or invalidity. Therefore, the development of management data information in Al-Wathoniyah Islamic Boarding School 43 North Jakarta will be a resource that can determine the progress of Islamic boarding schools in the future. Therefore, in this final project, a computerized Santori Data Registration Information System was developed as a tool to process new student data at Al-Wathoniyah Islamic Boarding School 43, North Jakarta.